Is Every Definition Persuasive? Douglas Walton on Persuasiveness of Definition - Pruś, Jakub; Aberdein, Andrew (Informal Logic, 2022)
“Is every definition persuasive?” If essentialist views on definition are rejected and a pragmatic account adopted, where defining is a speech act which fixes the meaning of a term, then a problem arises: if meanings are not fixed by the essence of being itself, is not every definition persuasive? To address the problem, we refer to Douglas Walton’s impressive intellectual heritage—specifically on the argumentative potential of definition. In finding some non-persuasive definitions, we show not every definition is persuasive. The persuasiveness lies not in syntactic or semantic properties, but the context. We present this pragmatic account and provide rules for analysing and evaluating persuasive definition—a promising direction for further research.